Hydration-mediated co-assembly enables whole-component utilization of flaxseed - Yanwen Sun; Xiangyang Liu; Xinyue Liu; Wanjun Han; Wei Yang; Yuanfa Liu (Food Hydrocolloids, 2026)

Selective partitioning of plant proteins during emulsification impairs foam stability: conformational changes of aqueous-phase residues relative to animal proteins - Yiqiu Deng; Wanjun Han; Yiting Lin; Xiuhang Chai; Fengxiang Chen; Yuanfa Liu (Food Hydrocolloids, 2026)

Amphiregulin as a central dynamic network biomarker in inhaled polyhexamethylene guanidine triggered pulmonary fibrosis - Jianzhong Zhang; Xin Li; Yuxin Ma; Wanjun Zhang; Zihao Han; Yanting Li; Jiayin Sun; Siqi Wang; Wei Han; Jing Liu; Yuxin Zheng; Jinglong Tang (Journal of Hazardous Materials, 2026)

Resilient Optimal Dispatch of Ship-Integrated Energy System and Air Lubrication Using an Enhanced Traffic Jam Optimizer - Wanjun Han; Jinlong Cui; Xinyu Wang; Xiaotao Chen (Journal of Marine Science and Engineering, 2026)
With increasingly stringent greenhouse gas emission regulations in the shipping industry, there is an urgent need for an efficient energy management strategy for new energy ship power systems. However, existing dispatch models often overlook the dynamic energy-saving potential of active drag reduction technologies and lack effective optimization algorithms capable of handling high-dimensional, multi-constrained problems. To address these problems, this paper proposes a novel integrated dispatch framework for hybrid energy ship power systems that incorporates air lubrication systems. First, a unified multi-energy dispatch model is established, coupling the dynamic operation of air lubrication systems with electrical, thermal, and propulsion energy flows. Second, an Improved Traffic Jam Optimizer algorithm is proposed, which enhances global exploration and local exploitation through a nonlinear parameter adaptation mechanism, differential mutation strategy, and dynamic hybrid search architecture. Convergence analysis based on Markov chain theory is provided to guarantee algorithmic reliability. Simulation results demonstrate that the proposed algorithm outperforms existing methods in terms of convergence speed, solution accuracy, and stability. Furthermore, integrating air lubrication systems into the ship power system reduces total operating costs and greenhouse gas emissions by up to 20.569% and 6.310%, respectively.

Protein “memory effect” induced by a heat transfer-directed precooling strategy enhances milk cream foam stability - Yiqiu Deng; Xiuhang Chai; Wanjun Han; Yuanfa Liu; Wengao Wang (Food Research International, 2026)

Plasma exosomes reveal insights into bovine tuberculosis pathogenesis and diagnostic opportunities - Hangfan Zhou; Qilong Zhang; Songhao Jiang; Han Yang; Shujie Cui; Wenhui Wu; Lei Chang; Wanjun Zhang; Yuping Xie; Jiaqiang Zhu; Degang Zhou; Yao Zhang; et al. (Veterinary Microbiology, 2026)

Synergistic interaction between hydrophilic polyglycerol fatty acid esters and sucrose esters regulates fat crystallization at the water/oil interface in highly unsaturated whipped emulsions - Wanjun Han; Yiqiu Deng; Yiting Lin; Farah Zaaboul; Qiuling Huangfu; Yanwen Sun; Xiuhang Chai; Chin-Ping Tan; Yuanfa Liu (Chemical Engineering Journal, 2025)

Destabilization mechanism of whipped cream during freeze-thaw cycles - Qiuling Huangfu; Wanjun Han; Yuanfa Liu; Xiuhang Chai; Wei Yang (Journal of Food Engineering, 2025)

The influence of synergistic interaction between raw milk protein and sodium caseinate on the interfacial stability of raw milk-based whipped emulsion - Yiqiu Deng; Wanjun Han; Xiuhang Chai; Yuanfa Liu (Food Hydrocolloids, 2025)

Synergistic effect of hydrophilic polyglycerol fatty acid esters and protein on the stability of interfacial membrane in low-fat aerated emulsions with different homogenization conditions - Wanjun Han; Xiuhang Chai; Farah Zaaboul; Yanwen Sun; Chin-Ping Tan; Yuanfa Liu (Food Chemistry, 2024)

Environmental quality assessment of heavy metals in the Rongcheng offshore area, Shandong Peninsula, China - Nana Yue; Congbo Xiong; Yongqiang Zhang; Wanjun Zhang; Yongcai Feng; Xia Li; Longzhi Han (Marine Pollution Bulletin, 2024)

Different hydrophilic polyglycerol fatty acid esters interact with fat crystals and proteins at the interface to co-stabilize highly unsaturated whipped emulsions - Wanjun Han; Xiuhang Chai; Yanwen Sun; Farah Zaaboul; Chin-Ping Tan; Yuanfa Liu (Food Hydrocolloids, 2024)

Corrigendum to “Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC-MS” [Food Chem. 414 (2023) 135739] - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

A novel 3D-fluorescence sensing strategy based on HN-chitosan polymer probe for rapid identification and quantification of potential adulteration in saffron - Wanjun Long; Gaoqiong Deng; Yanmei Zhu; Qingyang Han; Hengye Chen; Yuanbin She; Haiyan Fu (Food Chemistry, 2023)

Effect of different chain lengths of monoglyceride on the O/W interfacial properties with high-melting and low-melting crystals in low-fat aerated emulsion - Wanjun Han; Xiuhang Chai; Farah Zaaboul; Yanwen Sun; Chin-Ping Tan; Yuanfa Liu (Food Chemistry, 2023)

Design and fabrication of energetic Al/Ni exploding foil with enhanced energy efficiency and plasma density for direct ignition - Kehua Han; Xin Zeng; Wanjun Zhao; Jiao Li; Enyi Chu; Qingjie Jiao (Fuel, 2023)

Endogenous salicylic acid mediates melatonin-induced chilling-and oxidative-stress tolerance in harvested kiwifruit - Wanjun Guo; Chuyao Zhang; Ruiqin Yang; Siyi Zhao; Xinru Han; Zhiying Wang; Sufang Li; Hui Gao (Postharvest Biology and Technology, 2023)

Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC–MS - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

Pickering emulsions stabilized by hemp protein nanoparticles: Tuning the emulsion characteristics by adjusting anti-solvent precipitation - Yanwen Sun; Xiuhang Chai; Wanjun Han; Zaaboul Farah; Tian Tian; Yong-Jiang Xu; Yuanfa Liu (Food Hydrocolloids, 2023)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Assessing SARS-CoV-2 RNA levels and lymphocyte/T cell counts in COVID-19 patients revealed initial immune status as a major determinant of disease severity - Mingfeng Han; Mengyuan Xu; Yafei Zhang; Zhongping Liu; Shasha Li; Tengfei He; Jinsong Li; Yong Gao; Wanjun Liu; Tuantuan Li; Zixiang Chen; Xin Huang; et al. (Medical Microbiology and Immunology, 2020)